2022
DOI: 10.1111/nyas.14732
|View full text |Cite
|
Sign up to set email alerts
|

Combining vascular and nerve fiber layer thickness measurements to model glaucomatous focal visual field loss

Abstract: We compare the focal structure–function correlation of structural measurements of peripapillary retinal nerve fiber layer thickness (RNFL‐T) using optical coherence tomography (OCT), capillary density (CD) measurements using OCT‐angiography (OCT‐A), or a combination of both, with visual field deviation (VFD) in early to advanced glaucoma. Primary open angle glaucoma patients (n = 46, mean ± SD age: 67 ± 10 years; VF mean deviation: −10.41 ± 6.76 dB) were included in this cross‐sectional study. We performed 30–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…This floor level, which has been reported to range from −8 to −12 dB in other studies, 18,33,34,36,37 can also be inferred from the flattening of the VF MD estimations at around the −10 dB level with the LR models in Figure 1. In our study and others using nonlinear approaches based on decision trees, support vectors, or neural networks, a pertinent question to ask is why these difficulties at higher severities remain?-even in nonlinear models trained with relatively larger datasets.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This floor level, which has been reported to range from −8 to −12 dB in other studies, 18,33,34,36,37 can also be inferred from the flattening of the VF MD estimations at around the −10 dB level with the LR models in Figure 1. In our study and others using nonlinear approaches based on decision trees, support vectors, or neural networks, a pertinent question to ask is why these difficulties at higher severities remain?-even in nonlinear models trained with relatively larger datasets.…”
Section: Discussionsupporting
confidence: 73%
“…While different models could be trained for different severities, this would ostensibly require predetermination of disease severities using an additional classification model, or the use of anatomical compensation 39 to adjust RNFL measurements for interindividual demographic differences to better stratify disease severity. Inclusion of vascular information from OCT angiography, which we and others have shown to be less susceptible to floor effects, could also help to improve the structure–function association, 40–43 particularly in more advanced glaucoma 37 . These and other strategies, such as the use of repeated VF data to reduce VF variability or a more precise determination of neuronal content in the RNFL, 44 can be considered in future studies to further improve the VF estimation to allow these models to be used clinically.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It should be also mentioned that it seems that in glaucoma eyes, practically all vascular plexuses measured by OCTA around the optic disc and also in the macula, be it in-depth or horizontally (perifoveal/parafoveal), are affected 18 , 19 , 20 . Also, it is the combination of the OCT structural data and OCTA data that correlates best with the observed focal VF defects 21 .…”
Section: Discussionmentioning
confidence: 99%
“…OCT angiography studies have consistently demonstrated a reduction in capillary density in the macular region as well as in the peripapillary region in patients with early and manifest glaucoma [ 28 , 29 ]. Recently, it has been reported that there is a strong association between local perfusion defects and local visual field changes in glaucoma [ 30 , 31 , 32 , 33 , 34 ], indicating that at least part of the vascular changes is the result of reduced metabolic demand secondary to retinal ganglion cell loss.…”
Section: Discussionmentioning
confidence: 99%